PENGARUH MODEL PEMBELAJARAN BERBASIS PROYEK TERHADAP KETERAMPILAN PROSES SAINS DAN MOTIVASI BELAJAR SISWA SMPIT INSAN MANDIRI JAGAKARSA PADA PEMBELAJARAN IPAS - Nawangsari, Okky; Suharini, Erni; Widiyatmoko, Arif; Isdaryanti, Barokah; Tatang Khalid Mawardi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The purpose of this study was to determine the effect of the project-based learning model on the science process skills and learning motivation of students at SMPIT Insan Mandiri Jagakarsa in the IPAS subject regarding environmental change. The method used was a quasi-experiment with a pretest-posttest nonequivalent control group design. Data analysis techniques employed descriptive statistical analysis and hypothesis testing using either the Independent Sample T Test or Mann Whitney U Test at a significance level of 0.05. The results showed that the average posttest score of the control class was 51.35, while that of the experimental class was 79.15. This indicates that the average posttest score of the experimental class was higher than that of the control class. Furthermore, the hypothesis test using the Mann Whitney U Test yielded a significance value of <0.001 (sig. < 0.05), meaning that Ha is accepted, or there is a significant difference in science process skills between the experimental and control classes. Subsequently, descriptive analysis of student learning motivation data revealed an average final score of 77.85 for the control class and 82.40 for the experimental class. These results indicate that the final average of the experimental class is higher than that of the control class. In addition, the hypothesis test using the Independent Sample T Test obtained a significance value of 0.017 (sig. < 0.05), which means that Ha is accepted, or there is a significant difference in learning motivation between the experimental and control classes. Therefore, it is concluded that the project-based learning model has an effect on the science process skills and learning motivation of SMPIT Insan Mandiri Jagakarsa students in IPAS learning on the topic of environmental change.